Cyber Public Relations Strategies for Enhancing Public Engagement: A Case Study of Koja Hospital Instagram - Leila Mona Ganiem; Anna Agustina (Athena: Journal of Social, Culture and Society, 2023)
The rapid development of information technology that triggers transformation in the field of public relations has driven hospitals to implement cyber public relations in their organizational communication activities. This research analyzes the management of cyber public relations in one of Jakarta's regional general hospitals or health houses, namely the Koja Hospital. This study aims to explore Koja Hospital's efforts in interacting with the public through Instagram social media. Data mining will focus on two aspects: first, what messages Koja Hospital conveys through Instagram, and second, how the public reacts to messages from Koja Hospital. The research method used is a mixed, qualitative, and quantitative method. The quantitative method is used to mine data related to the messages conveyed by Koja Hospital through Instagram, while the qualitative method is used to explore how Koja Hospital manages dialogues with the public on its Instagram account. This research is conducted by analyzing Koja Hospital's Instagram account from January-February 2023. The research findings conclude that Koja Hospital uses Instagram as a cyber public relations platform to convey messages with categories including Health Education, Service Promotion, Hospital Social Programs, Employee Activities, Events, Health Technology Innovations, and Awards and Certifications through photos and videos. However, engagement with users is still not optimized. In conclusion, cyber public relations should utilize all features provided by social media platforms, produce messages optimally, and engage with users interactively